Implementing standards of care for heart failure patients in general practice – the IMPACT-B study protocol. Issue 5 (16th July 2021) - Raat, Willem; Smeets, Miek; Van Pottelbergh, Gijs; Van de Putte, Marie; Janssens, Stefan; Vaes, Bert
Abstract: Background: Heart failure (HF) is an important health problem. Most chronic HF management occurs in primary care. Although guidelines exist, there is an important implementation gap in current HF care in Belgium. Methods: We will conduct a non-randomised, non-controlled prospective observational trial to implement guideline-recommended disease management interventions in primary care in Leuven, a region of ±100.000 inhabitants. These interventions include education of general practitioners, reimbursement of the analysis of circulating natriuretic peptides and audits in the electronic health record (EHR), training and implementation of HF educators in primary care, and a protocol to structure transition to primary care after discharge. The main objective is to study and implement interventions in an iterative implementation process. Conclusions: We will evaluate the implementation of several guideline-recommended disease management interventions to optimise the diagnosis and treatment of heart failure in a real-world primary care setting. Trial registration: NCT04334447 (clinicaltrials.gov)